Neuropsychological and biopsychosocial evolution, therapeutic adherence and unmet care needs during paediatric transplantation: study protocol of a mixed-methods design (observational cohort study and focus groups) – the TransplantKIDS mental health project - Garrido-Bolton, Jessica; Alcamí-Pertejo, Margarita; de la Vega, Rocío; Hernández-Oliveros, Francisco; Pérez-Martínez, Antonio; Bravo-Ortiz, María Fe; Fernández-Jiménez, Eduardo (Frontiers in Psychology, 2024)
The present article describes the protocol of a mixed-methods study (an observational cohort design and focus groups), aimed to examine biopsychosocial and neuropsychological functioning and other biopsychosocial outcomes, unmet care needs and predictors of therapeutic adherence and unmet care needs in paediatric population among children and adolescents undergoing solid organ or allogeneic hematopoietic transplant during the pre-and post-transplant phases. The following hypotheses were formulated: H1. There will be significant improvement in different biopsychological and neuropsychological domains 6 months post-transplant; H2. Executive functioning will mediate the relationship between several biopsychological outcomes and therapeutic adherence; H3. Differences in biopsychosocial and neuropsychological functioning and therapeutic adherence will be observed between transplant types. Following a multi-method/multi-source approach, neuropsychological domains will be comprehensively measured with objective tests (SDMT, K-CPT 2/CPT 3, TAVECI/TAVEC, WISC-V/WAIS-IV Vocabulary and Digit Span subtests, Verbal Fluency tests, Stroop, ROCF, and TONI-4); ecological executive functioning, affective and behavioural domains, pain intensity/interference, sleep quality and therapeutic adherence will be assessed through questionnaires (parent/legal guardians-reported: BRIEF-2 and BASC-3; and self-reported: BASC-3, BPI, PROMIS, AIQ and SMAQ); and blood levels of prescribed drugs will be taken from each patient's medical history. These outcomes will be measured at pre-transplant and at 4-weeks and 6-months posttransplant phases. The estimated sample size was 60 patients (any type of transplant, solid organ, or hematopoietic) from La Paz University Hospital (Madrid, Spain). Individual pre-and post-transplant psychological assessments (at 4 weeks and 6 months post-transplant) will be carried out, to be completed by both patients and their parents/legal guardians, as well as in individual and face-to-face neuropsychological testing sessions. Finally, three focus group sessions will be organized with patients, their relativesparents/guardians, and transplant clinicians the medical-surgical professionals in charge of them (n = 15, with 5 participants per group), in order to qualitatively identify unmet care needs during the pre-, and post-transplant care processstages of the process. The study protocol was registered at ClinicalTrials. gov (NCT05441436).